Técnica didáctica artística CADADI (canto, Danza y Dibujo) y su influencia en el aprendizaje relevante en alumnos de Educación Primaria de Rioja - Ayapi Bazán, Patricia (2002)
The present experimental investigation was carried out with the educandos of the fourth grade of Primary Education of the Educational Center No. 00537 Matilde of the Eagle Velásquez, belonging to the city of Rioja, region of San Martin. The problem, hypothesis and general objective have been structured by means of the relationship of the Artistic didactic technical variables CADADI (I Sing, it Dances and Drawing) and the outstanding learning. The theoretical body of the Artistic didactic technique CADADI (I Sing, it Dances and Drawing) he/she was systematized endowing him of a purpose, of an action field, of pre didactic processes (dialogue, negotiation, culture experiencial of the educating), of didactic processes (I sing, it dances and drawing) and of a theoretical support based on the materialistic philosophical foundation regarding the art, in the biology of the learning and in the psicopedagogía piagetiana. Hypothesis was formulated: the alternating hypothesis whose presumption was the significant influence of the outstanding learning with the experimentation of the Artistic didactic technique CADADI (1 Sing, it Dances and Drawing) and the null hypothesis that predicted the it doesn't influence significant of the outstanding learning. The studied population the they conformed 95 educandos to who you/they were evaluated by means of a pre and post test to determine the significant influence or not of the Artistic didactic technique CADADI (I Sing, it Dances and Drawing) in the outstanding learning. The sample was chosen using the chart of random numbers for the educandos assignrnent to the experimental group and control aleatorily. In the first group they conformed it 17 educandos and in the second 26 educandos, obtaining a size of representative and appropriate sample of 43 educandos. In consequence, the conclusions reveal that the Artistic didactic technique CADADI (I Sing, it Dances and Drawing) it stimulates the artistic activities associated to the science, art and thought, it cooperates to the formation of the social conscience of the educandos and it is appropriate for the development of classes where it prevails the thought and the action, bearing to the materialization of an evident outstanding learning in conceptual, procedural competitions and actitudinales.